IMPACT AND GROWTH OF THE INTERNET IN THE LAST YEARS - Vieira, Gustavo; Dian, Mauricio de Oliveira (Revista Interface Tecnológica, 2023)
This article focuses on the increasing expansion of Internet usage in recent years and the corresponding efforts by telecommunications companies to meet the growing demand for connectivity services. The COVID-19 pandemic has further accelerated the digital transformation worldwide, highlighting the vital role of connectivity in both personal and professional lives. Telecom companies have responded to this trend by investing in infrastructure and technology to ensure high-quality and reliable internet services. The objective of this article is to present data, information, and statistics collected from various sources, including web research, articles, and magazines, to emphasize the growth and importance of the Internet. Understanding the crucial role of the Internet in economic and social development is essential, as it contributes to job creation, improved education and healthcare, and creates new opportunities for business and innovation. Throughout the article, it becomes evident that the expansion of the Internet, particularly during the pandemic, has led to an increased number of connected users, highlighting society’s growing dependence on this technology.